2021
DOI: 10.31943/afiasi.v6i2.151
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Pencegahan dan Sumber Informasi Covid 19 di Perdesaan dan Perkotaan

Abstract: Abstrak Kasus Covid-19 masih bertambah tetapi perilaku pencegahan penularan 3-M yaitu memakai masker, mencuci tangan dengan sabun serta menjaga jarak belum dilakukan seluruh masyarakat. Penelitian bertujuan mengetahui pengaruh jenis tempat tinggal (perdesaan, perkotaan) terhadap perilaku pencegahan Covid-19 dengan mempertimbangkan akses sumber informasi. Metode penelitian kuantitatif dengan pendekatan cross sectional. Populasi penelitian masyarakat Jawa Barat dengan multi stage cluster dan purposive samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…This study shows that pregnant women's knowledge of clean and healthy living behavior in preventing COVID-19 in rural areas is higher than in urban areas. In line with the results of previous studies where knowledge of COVID-19 in rural areas is higher than in urban areas (Surtimanah et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…This study shows that pregnant women's knowledge of clean and healthy living behavior in preventing COVID-19 in rural areas is higher than in urban areas. In line with the results of previous studies where knowledge of COVID-19 in rural areas is higher than in urban areas (Surtimanah et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…This is supported by an Indonesian study conducted in West Java Province where they found that the source of COVID-19 information was strongly and significantly associated with preventive behavior. That study also discovered that their major source of information came from respected public figures (83.7%) and the local government announcement (74.7%) ( 52 ).…”
Section: Discussionmentioning
confidence: 84%
“…Dua SD yang dijadikan subjek penelitian ini berada di perkotaan, perlu telaah lebih lanjut apakah pengetahuan siswa SD di perdesaan sama atau berbeda. Penelitian terdahulu mengemukakan adanya perbedaan pengetahuan tentang COVID-19 antara masyarakat yang tinggal di perdesaan dan perkotaaan [12] . Hasil penelitian ini menunjukan sebanyak 66,3% siswa memiliki pengetahuan tentang COVID-19 termasuk upaya pencegahannya dalam kategori baik.…”
Section: Pembahasanunclassified